Sistem Pendukung Keputusan Penentuan Status Karyawan Menggunakan Metode Naive Bayes (Studi Kasus: PT. Emsonic Indonesia) - Andri Firmansyah; Feri Ramdhani (Jurnal SIGMA, 2020)
Abstract In this study formulated the problem of how to implement the naïve Bayes method in determining employee status decisions, so as to accelerate and facilitate decision making in determining the status of interns to become contract employees at PT EMSONIC INDONESIA. This study aims to predict the eligibility of an intern to become a contract employee. The naïve Bayes method uses employee criteria as training data and calculates the data to get the probability value so that the probability value can predict the outcome of the decision whether an employee is eligible or not to change his status. In building a decision support system to determine employee status, Visual Studio 2010 is used, and also uses MySql as a database to store the data used. Application of decision support systems using the Naive Bayes method can be a reference in determining employee status. The results of the decision support system using the naïve Bayes method are proven to be able to predict accurately the eligibility of employee status, with an accuracy value of 89.5%. Keywords: decision support system, naïve bayes, visual studio, MySql